2018
DOI: 10.3393/ac.2017.06.12
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcome of a Fissurectomy: A Prospective Single-Arm Study of 50 Operations out of 349 Initial Patients

Abstract: Purpose The surgical standard of care for patients with chronic anal fissure is still disputed. We aimed to assess the natural course of idiopathic anal fissure and the long-term outcome of a fissurectomy as a surgical treatment.Methods All consecutive patients referred to a single expert practitioner in a tertiary centre were primarily included. A fissurectomy was proposed in cases of refractory symptoms after 4 to 6 weeks of standard medical management. Only patients with idiopathic and noninfected anal fiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 16 publications
1
12
1
Order By: Relevance
“…Fissurectomy is one of the options among those techniques to treat chronic anal fissures. Many surgeons used this technique in patients with a high risk of incontinence, such as old age people, multiparous women, patients with the normal anal tone, and patients with a previous history of anorectal surgery [ 9 ]. Some studies showed that patients with chronic fissures who are refractory to medical treatment responded well to fissurectomy [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fissurectomy is one of the options among those techniques to treat chronic anal fissures. Many surgeons used this technique in patients with a high risk of incontinence, such as old age people, multiparous women, patients with the normal anal tone, and patients with a previous history of anorectal surgery [ 9 ]. Some studies showed that patients with chronic fissures who are refractory to medical treatment responded well to fissurectomy [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This latter surgical procedure has been associated with pharmacological sphincterotomy to improve its results, as well as reduce its complications [ 15 20 ]. After surgical fissurectomy, with or without association with chemical sphincterotomy [ 13 , 15 , 21 26 ], we observe a complete second intention wound healing, even after 10 weeks and the rate of failure con reach the 34% [ 24 ]. The rate of recurrence reaches up to the 37% in some series [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fissurectomy was described for the first time in 1930 by Gabriel for adult patients and since then, it has been one of the main treatments for anal fissure in the German Coloproctologist community [9]. Fissurectomy has also been used to remove the fibrotic tissue in paediatric patients [26]. A relatively recent suggestion was to combine a botulinum toxin A injection with fissurectomy in case treatment involving only botulinum toxin A injection failed [13].…”
Section: Treatment Strategies and Safetymentioning
confidence: 99%